2017
DOI: 10.1242/jeb.155069
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids buffer the acute phase response on fever, sickness behavior, and rapid bill color change in zebra finches

Abstract: Carotenoids are finite resources that animals can allocate to selfmaintenance, attractiveness or reproduction. Here we test how carotenoids affect the acute phase response (APR), an intense rapid systemic response characterized by fever, sickness behavior and production of acute phase proteins, which serves to reduce pathogen persistence. We conducted a 2×2 factorial design experiment in captive adult male and female zebra finches (Taeniopygia guttata) to determine the effects of carotenoid supplementation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Previous studies have shown the categorical perception of behaviourally or ecologically important stimuli, for example, in discriminating between different speech phonemes [11] or birdsong note types [4], predators versus conspecifics [3], or potential mates [2,8], but studies have not compared the perception of similar stimuli across different functional contexts. Male zebra finch beak colours range from light orange to dark red [13], and females show a mating preference for males having redder beaks [43,44], a preference thought to be driven by the fact that the expression of carotenoid-based red coloration correlates positively with variation in cell-mediated immunity in this species [13,45,46]. The sharper category boundary observed in the orange -red colour range may therefore be the result of selection on communicative function in the context of mate choice.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown the categorical perception of behaviourally or ecologically important stimuli, for example, in discriminating between different speech phonemes [11] or birdsong note types [4], predators versus conspecifics [3], or potential mates [2,8], but studies have not compared the perception of similar stimuli across different functional contexts. Male zebra finch beak colours range from light orange to dark red [13], and females show a mating preference for males having redder beaks [43,44], a preference thought to be driven by the fact that the expression of carotenoid-based red coloration correlates positively with variation in cell-mediated immunity in this species [13,45,46]. The sharper category boundary observed in the orange -red colour range may therefore be the result of selection on communicative function in the context of mate choice.…”
Section: Discussionmentioning
confidence: 97%
“…2000), Complete Freund's Adjuvant (George et al . 2017) or lipopolysaccharide of Escherichia coli (Alonso‐Álvarez et al . 2004)) or by comparing the immune defences of individuals with bright and dull ornaments (Dunn et al .…”
Section: Parameters Constraining Carotenoid Signal Expressionmentioning
confidence: 99%
“…Previous studies have linked the orange to red color continuum of male zebra finch bills with immune function (Blount et al, 2003;deKogel & Prijs, 1996;George et al, 2017;McGraw & Ardia, 2003; but see Birkhead et al, 1998), suggesting that bill color may reflect individual quality and, by extension, competitive ability. However, although one behavioral study has supported the role of carotenoidbased colors in aggressive signaling (Ardia et al, 2010), others have found no evidence of a signaling function (Bolund et al, 2007;Burley & Coopersmith, 1987;Etman et al, 2001).…”
mentioning
confidence: 98%